Crystallisation and crystal structure studies of some TCNQ salts - Houghton, Timothy James (1980)
A series of salts of the radical ion TCNQ were prepared by standard organic techniques or by controlled electrocrystallisation and their three-dimensional crystal structures were determined by single crystal X-ray diffractometry. The crystallisation of the two-phase system found in 1,2-bis(1-ethyl-4-pyridinio)ethene (TCNQ)4 was studied using a.c. conductivity techniques. The results showed phase formation to be dependent upon both concentration and cooling rate, and no evidence was found for a third phase possessing a metallic d.c. solid state conductivity. The structures reported in detail are: a) 1,4-dimethylpyridinium (TCNQ)2' DMPY(TCNQ)2' Triclinic, a = 7.833, b = 13.889, c -7.171Angstrem, alpha = 106.81, beta = 112.50, gamma = 95.36°, z = 1, space group P1. TCNQ moieties stacked as discrete diads with an interplanar separation of 3.21 Angstrem within the diad. The d.c. dark conductivity was measured (sigma 300 = 1.7 x 10 (-4) ohm cm (-1)) and is consistent with the observed structure. b) 2,3-bis(1-methyl-4-pyridinio)butane (TCNQ)4' DMPB (TCNQ)4, Triclinic, a = 7.798, b = 14.248, c = 13.690 Angstrem, alpha = 109.53, beta = 103.37, gamma = 95.42°, Z = 1, space group P1. TCNQ moieties stacked as discrete tetrads with interplanar separations of 3.13 and 3.17 Angstrem within the tetrad. Anisotropic d.c. dark conductivity measurements were made and found to be consistent with the structure. c) 1,2-bis(1-hydro-4-pyridinio)ethane (TCNQ)2, DHPA (TCNQ)2, monoclinic, a = 29.481, b = 7.405, c = 13.470 grad., beta = 94.03 grad., Z = 4, space group 2/c. TCNQ moieties arranged in 4 columns of diads along c with an interplanar separation of 3.10 Angstrem within the diad. The structure exhibits hydrogen bonding (N - H--------N heavy atom separation = 2.885 Angstrem) between the cation and TCNQ moieties. d) 1,2-bis(1-hydro-4-pyridinio)ethane (TCNQ)4, DHPA (TCNQ)4, monoclinic, a = 12.894, b = 3.933, c = 27.580 grad., beta = 109.95 grad., Z = 1, space group P 21/c .TCNQ moieties in infinite stacks along b with cations in disordered positions in the channels between the stacks.